Bilateral theta‐burst stimulation on emotional processing in major depressive disorder: A functional neuroimaging study from a randomized, double‐blind, sham‐controlled trial. Issue 4 (3rd February 2023) - Chou, Po‐Han; Tu, Cheng‐Hao; Chen, Chun‐Ming; Lu, Ming‐Kuei; Tsai, Chon‐Haw; Hsieh, Wan‐Ting; Lai, Hui‐Chen; Satyanarayanan, Senthil Kumaran; Su, Kuan‐Pin
Abstract : Aim: Bilateral theta‐burst stimulation (biTBS; intermittent TBS over the left dorsolateral prefrontal cortex [DLPFC] and continuous TBS over the right DLPFC) has demonstrated efficacy in improving symptoms in patients with major depressive disorder (MDD). However, the underlying brain mechanisms remain unknown. The authors aimed to investigate the antidepressant efficacy of biTBS monotherapy and its effects on the brain responses measured by functional magnetic resonance imaging (fMRI) during emotional processing in MDD. Methods: The authors conducted a double‐blind, randomized, sham‐controlled trial of patients with MDD who exhibited no responses to at least one adequate antidepressant treatment for the prevailing episode. Recruited patients were randomly assigned to 10 biTBS monotherapy or sham stimulation sessions. The fMRI scans during performing emotional recognition task were obtained at baseline and after 10 sessions of treatment. Depressive symptoms were assessed using the 21‐item Hamilton Rating Scale for Depression at baseline and the weeks 4, 8, 12, 16, 20, and 24 week. Results: The biTBS group ( n = 17) exhibited significant decreases in depression scores compared with the sham group ( n = 11) at week 8 (70% vs 40%; P = 0.02), and the significant differences persisted during the 24‐week follow‐up periods. At week 4, when the treatment course was completed, patients in the biTBS group, but not in the sham group, exhibited increased brain activities over the left superior and middle frontal gyrus during negative emotional stimuli. Conclusion: The authors' findings provide the first evidence regarding the underlying neural mechanisms of biTBS therapy to improve clinical symptoms in patients with MDD.